Peran Karakter Individu dan Lingkungan Kerja dalam Meningkatkan Kinerja dan Kepuasan Layanan Rumah Sakit Aloe Saboe Gorontalo - Husain, Anggriani; Poppy Mujizat; Rizkina Fauzia Ansar; Leydia Asterina Syahrain; Muh. Sabir Mustafa (Al-Buhuts, 2025)
This study aims to explore the impact of individual characteristics and work environment on service performance and user satisfaction at Aloe Saboe Hospital, Gorontalo. The subjects of this study were healthcare workers and patients at the hospital. The research method employed a quantitative approach with data analysis using Partial Least Squares - Path Modeling (PLS-PM). Data were collected through observation, questionnaires, and literature review. The findings indicate that individual characteristics, such as empathy and communication skills, along with a supportive work environment, significantly contribute to improved service performance and user satisfaction